Low-Cost Data Acquisition Station for Microclimate Detection and Public Health Risks Management: A Case Study of Casablanca - Youness, Akensous; Mustapha, Hakdaoui; Sultan, Al-Akad; Ahmed, Al Sabri (International Journal of Online and Biomedical Engineering (iJOE), 2020)
the environmental data acquisition station is used to manage the public health and detection of a microclimate of a city for a broadcast processed high precision data for users. This research article is summarizing the applications of Electronics and GIS applications to health risks management due to air pollution, noise and microclimate change detection, to study the geography of urban health risks and environmental change in Casablanca, Morocco. acquisition of environmental and Climatological Data using sensor networks, results a new possibilities and advantages, of environmental data monitoring using electronic circuit with a broadcasting system via a technology with wireless transmitter. The main object of this research is to present a simple and rapid method to provide instant microclimate and environment data, which can be used to manage the public risks caused by pollution and environment changes. As the climate and environment conditions are variable from a place to place, it is difficult to get accurate climate and environment for a particular location in a city. With the advancement of technology, especially data acquisition systems, the problem of large set up area and cost has been reduced. The data acquisition station can be set up at any place and provide an accurate and instant climate and environment report to any citizen of the city. The report of the data acquisition system can be used by the users to choose the best place for them to live due to their diseases. In addition, these data can be collected in a GIS system to create a microclimate change and air pollution map of different zones in the city, predict the future climate, and air pollution of the city.